Early breastfeeding and complementary feeding in Ethiopia: cross-sectional data from implementation of nutrition programming on regional inequalities. Issue 4 (April 2021) - Potts, Kaitlin S.; Asaba, Megumi; Mulugeta, Afework; Bazzano, Alessandra N.
Abstract: Improving nutrition for young children remains an urgent priority globally. Ethiopia has made great strides over the last two decades in improving health and nutrition for children. The task of scaling improved nutrition services now turns to addressing progress on the regional level. This research sought to highlight regional disparities identified in scaling nutrition services for child nutrition in Ethiopia, by identifying variations in early breastfeeding and child feeding practices and associated socio-demographic characteristics by geographic area in four regions of the country. The cross-sectional study data derived from an evaluation of nutrition services and programming and included 1299 participants, of whom 50% reported practicing recommended early breastfeeding practices. This varied from less than 8% in one zone of Afar region to 84% in a zone of Tigray, with differences also noted by socio-demographic characteristics. Among the total sample, 70% of respondents met the recommendation for minimum number of feedings per day, and 16% met the recommendation for dietary diversity. Less than 8% of families in the service population in Northwestern Tigray zone met the dietary diversity recommendation compared to 36% in South Wollo, Amhara region. Utilizing regional and zonal data will allow for government and other agencies involved in improving nutrition and health outcomes to appropriately provide services and programs for families and children over the life course. Abstract : Dietary diversity; Nutritional adequacy; Lactation; Breast feeding; Child feeding; Malnutrition.